The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1049/iet-gtd.2013.0091
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic assessment of voltage dips caused by transformer energisation

Abstract: Energisation of large power transformers may cause significant voltage dips, of which the severity largely depends on a number of parameters, including circuit breaker closing time, transformer core residual flux and core saturation characteristic, and network conditions. Since most of the parameters are of stochastic nature, Monte Carlo simulation was conducted in this study to stochastically assess the voltage dips caused by transformer energisation in a 400 kV grid, using a network model developed and valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Hence, the validation study was conducted based on 1000 residual flux combinations stochastically generated based on the residual flux pattern and magnitude range suggested in Brunke and Frohlich . The method to generate the stochastic residual flux was detailed in Peng et al . and Peng .…”
Section: Network Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the validation study was conducted based on 1000 residual flux combinations stochastically generated based on the residual flux pattern and magnitude range suggested in Brunke and Frohlich . The method to generate the stochastic residual flux was detailed in Peng et al . and Peng .…”
Section: Network Model Validationmentioning
confidence: 99%
“…Hence, the validation study was conducted based on 1000 residual flux combinations stochastically generated based on the residual flux pattern and magnitude range suggested in Brunke and Frohlich. 27 The method to generate the stochastic residual flux was detailed in Peng et al 28 and Peng. 29 It was found that, to achieve a no more than 12% deviation to the measured inrush currents, the residual flux pattern should be zero, negative and positive for phases A, B and C, respectively, and the residual flux magnitude should be in the range between 0.275 and 0.311 pu of the peak nominal flux.…”
Section: Network Model Validationmentioning
confidence: 99%